Spectral Problems in the Monitoring of Distributed Safety Parameters of Objects in the Technosphere - Khlystunov, M. S.; Poduval’tsev, V. V.; Mogilyuk, Zh. G. (Measurement techniques, 2016)
Metrological aspects of the monitoring of distributed safety parameters of objects in the technosphere are discussed. Amplitude and phase frequency characteristics of the spectra of the spatial distribution of monitored parameters are presented for various sensor positioning schemes. A comparative analysis is made of the effect of the density and uniformity of sensor positioning schemes on the error of monitoring systems. A set of tasks is formulated for eliminating error in monitoring systems for multidimensional processes.